1997
DOI: 10.1111/j.1472-8206.1997.tb00854.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different ozone concentrations on the neurogenic contraction and relaxation of guinea pig airways

Abstract: Prejunctional and postjunctional effects of several ozone (O3) concentrations, including those found in highly polluted cities, were evaluated in guinea pig airways. Animals bred in O3-free conditions were exposed to air or O3 (0.3, 0.6 or 1.2 ppm) during 4 h, and studied 16-18 h later. Tracheal and bronchial rings were studied in organ baths. Electrical field stimulation (EFS) (100 V, 2 ms, 10 s) was given at increasing frequencies (0.25-16 Hz). Some tissues received atropine (2 microM) and/or propranolol (10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 16 publications
(20 reference statements)
2
6
0
Order By: Relevance
“…This finding clarified our previous observation related to the apparent tendency of tracheas exposed to 1.2 ppm O 3 to relax less than the control tissues. 2 Our current results clearly point out that O 3 indeed causes a post-junctional impairment of the adrenergic relaxation, which is revealed only when thoracic trachea is used.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…This finding clarified our previous observation related to the apparent tendency of tracheas exposed to 1.2 ppm O 3 to relax less than the control tissues. 2 Our current results clearly point out that O 3 indeed causes a post-junctional impairment of the adrenergic relaxation, which is revealed only when thoracic trachea is used.…”
Section: Discussionsupporting
confidence: 66%
“…5 Mediators involved in these pathways include epinephrine and norepinephrine, as well as nitric oxide and vasoactive intestinal peptide, respectively. 6 In a previous work 2 we reported that O 3 induced an impairment of prejunctional adrenergic relaxation without affecting the post-junctional guinea pig tracheal responses to isoproterenol (ISO) and sodium nitroprusside (NP), a well-known nitric oxide donor. Interestingly, in that study we found a tendency of tracheas exposed to 1.2 ppm to relax less than control tissues.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These include sympathetic nervous system activation, glucocorticoid release and NO production (Li & Quock, 2002; Sanchez et al 2003; Shalev, 2002). In this context, catecholamines and NO are two well‐known relaxing agents of the airway smooth muscle (Hamad et al 2003; Sommer et al 1997). Because the combination of propranolol and l ‐NAME abolished the low basal airway tone at the beginning of the plethysmographic session, it is reasonable to suggest that this phenomenon was mediated by the stress‐induced release of catecholamines and NO.…”
Section: Discussionmentioning
confidence: 99%
“…Some experiments were conducted in a Ca 2+ ‐free medium (with 0.1 m m of the Ca 2+ chelator EGTA), and other experiments used electrical field stimulation (EFS) with square pulses of 16 Hz, 2 ms and 100 V for 10 s delivered through platinum electrodes. It has been shown that this EFS protocol produces a biphasic response, with an initial cholinergic contraction followed by an adrenergic and non‐adrenergic relaxation (Sommer et al 1997). Four initial EFSs were sequentially delivered 10 min apart in order to corroborate their repeatability.…”
Section: Methodsmentioning
confidence: 99%